Optimization of debittering and deacidification parameters for Pomelo juice and assessment of juice quality - Gupta, Arun Kumar; Koch, Parismita; Mishra, Poonam (Journal of food science and technology, 2020)
Bitterness and tartness are one of the crucial reasons for the poor commerciality of Pomelo fruits. The present study intends to optimize the process variables such as resin concentration (Amberlite IRA-400) (3–10 g), time exposure (10–60 s), and stirring speed (300–1000 rpm) for removal of naringin content and tartness using response surface methodology. All the independent variables have shown a significant effect on naringin content, titrable acidity, and vitamin C content of pomelo juice. The optimized process variables for debittering and deacidification were 3.27 g resin concentration, 60 s time and 1000 rpm stirring speed, and the naringin content and titrable acidity at these optimized conditions were 0.22 mg ml −1 and 0.64% citric acid equivalent respectively. The treated juice under optimum conditions was analyzed for physicochemical properties where pH, clarity, and L* value of juice increased. In contrast, total soluble solids, vitamin C content, and a* value decreased slightly. The finding of present investigation will be helpful to improve the commercial acceptability of the sour variety of citrus fruit juice.